Visuospatial Function at Sub-Acute Phase Predicts Fatigue 10 Years After Stroke - Elgh, Eva; Hu, Xiaolei (Frontiers in Neurology, 2020)
Background and objective: Fatigue is common among stroke survivors; and has significant negative consequences. However, long-term follow-up on post-stroke fatigue and it’s association with cognitive and physiological parameters remains vague. Methods: A prospective cohort study was carried out on 38 young stroke survivors (aged 18–65 at stroke onset) living in the community ten years after first-ever stroke. Fatigue was assessed by Fatigue assessment scale (FAS). Global cognition and cognitive sub-domains were assessed repeatedly at one week, seven months, and ten years after their first-ever stroke. Univariate correlation analysis was used to investigate associations and multivariate regression was used to investigate predictors and association with fatigue. Results: At ten-year follow-up after stroke onset, more than half of the 38 participants suffered from fatigue (with median score 25 on FAS with 25-75% percentile (21-28)). Most of them were independent in their everyday life (mRS median score 1 (0-2)). In univariate correlation analyses, higher fatigue score was significantly correlated to higher independence in the daily activity, higher BMI, worse anxiety, higher scores on global cognition and better working memory at ten-year follow-up as well as better visuospatial functions after seven months and ten-years. In a multiple regression analysis, only visuospatial function at seven-month follow-up was a significant predictor of fatigue ten years after stroke onset (F (1, 4) 23.07, p=0.009), with adjusted R2 of 0.815) i.e. higher scores on Block design were associated with more fatigue. Conclusion: Our results extended the time course of post-stroke fatigue up to ten years after stroke onset. The participants with more fatigue performed better in cognitive assessments and daily activity, which indicated dissociation between fatigue and fatigability among stroke patients. Visuospatial function at the sub-acute phase predicted independently late post-stroke fatigue. This may offer a broad time window for rehabilitation and information about fatigue. The clinical implications of the current findings are worth to be studied further.